Neuromuscular electrical stimulation (NMES) reduces structural and functional losses of quadriceps muscle and improves health status in patients with knee osteoarthritis. Issue 4 (8th November 2012) - Vaz, Marco Aurélio; Baroni, Bruno Manfredini; Geremia, Jeam Marcel; Lanferdini, Fábio Juner; Mayer, Alexandre; Arampatzis, Adamantios; Herzog, Walter
Abstract Knee osteoarthritis (OA) is associated with quadriceps atrophy and weakness, so muscle strengthening is an important point in the rehabilitation process. Since pain and joint stiffness make it often difficult to use conventional strength exercises, neuromuscular electrical stimulation (NMES) may be an alternative approach for these patients. This study was aimed at (1) identifying the associations of knee OA with quadriceps muscle architecture and strength, and (2) quantifying the effects of a NMES training program on these parameters. In phase 1, 20 women with knee OA were compared with 10 healthy female, asymptomatic, age‐matched control subjects. In phase 2, 12 OA patients performed an 8‐week NMES strength training program. OA patients presented smaller vastus lateralis thickness (11.9 mm) and fascicle length (20.5%) than healthy subjects (14.1 mm; 24.5%), and also had a 23% smaller knee extensor torque compared to the control group. NMES training increased vastus lateralis thickness (from 12.6 to 14.2 mm) and fascicle length (from 19.6% to 24.6%). Additionally, NMES training increased the knee extensor torque by 8% and reduced joint pain, stiffness, and functional limitation. In conclusion, OA patients have decreased strength, muscle thickness, and fascicle length in the knee extensor musculature compared to control subjects. NMES training appears to offset the changes in quadriceps structure and function, as well as improve the health status in patients with knee OA. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 511–516, 2013